Peran Lingkungan dalam Pendidikan Islam Berdasarkan Perspektif Al-Qur’an: Pembentukan Karakter dan Tujuan Pendidikan - Dadan Nugraha; Ateng Ruhendi; Firgina Amelia Nur Husni (CV. Biha Cendekia, 2025)
This study aims to determine the concept of the Islamic educational environment from the perspective of the Qur'an. This study uses a technical library research in the literature review method including systematic identification, analysis of documents containing information related to the study problem through several available literature. Education seeks to nurture individuals and their development in humans, so the Qur'an seeks to educate all creatures including humans. The Qur'an also emphasizes the existence of educational goals, especially in training the soul and regulating behavior. Education is obtained from the environment including the family environment, the school environment/madrasah (Islamic boarding school), the community environment. This environment influences the formation of individual character so that they can achieve happiness in the world and the hereafter.